Pengaruh Pupuk Organik Cair dan Urea Terhadap Kemasaman, N-total, Serapan N, Serta Produksi Tanaman Selada (Lactuca sativa L) Pada Regosol - Darso, Widya A S P; Kaya, Elizabeth; La Habi, Maimuna (Universitas Pattimura, 2023)
The growth and yield of lettuce can be increased by improving soil fertility, both physical, chemical and biological conditions of soil, through fertilization. The fertilizer given can be organic fertilizer or non-organic fertilizer. Indirectly, soil type also influences vegetable growth and yield. This study aimed to explain the effect of a combination of liquid organic fertilizer and urea on Regosol soil pH, total N, plant N content and red lettuce (Latcuca sativa L) yield. The experiment used a factorial Randomized Block Design with 2 factors and 3 replications. The treatments tried consisted of liquid organic fertilizer with concentrations of 0 mL/L, 2 mL/L, 4 mL/L, and 6 mL/L, combined with Urea fertilizer at a dose of 0 g per pot, 0.3 g per pot, 0.6 g per pot, and 0.9 g per pot. The research results showed that applying liquid organic fertilizer at 6 mL/L of water combined with urea fertilizer at 0.6 g per pot was the best doses that could increase the pH and total N of Regosol soil, respectively with values of 6.03 and 0.27%, as well as increasing N uptake, number of leaves, and freshg weight of red lettuce plants, with respective values of 3.48%, 26.33 leaves, and 40 g.